Contact allergy in Danish children: Current trends. (9th August 2018) - Simonsen, Anne B.; Foss‐Skiftesvik, Majken H.; Thyssen, Jacob P.; Deleuran, Mette; Mortz, Charlotte G.; Zachariae, Claus; Skov, Lone; Osterballe, Morten; Funding, Anne; Avnstorp, Christian; Andersen, Bo L.; Vissing, Susanne; et al.
Abstract : Background: Contact allergy is common in children, but may be underdiagnosed. Importantly, the clinical relevance of specific allergies is subject to constant change, and it is therefore important to continuously monitor the trends and changes of contact allergies in the paediatric population. Objectives: To identify possible changes in contact allergy and allergic contact dermatitis among Danish children referred for patch testing. Methods: A retrospective study was performed based on patch test data from the Danish National Database of Contact allergy. The current data were compared with previously published data on Danish children referred for patch testing. Results: Between 2012 and 2016, 1573 children and adolescents were patch tested. Overall, 385 (24.5%) had at least 1 positive patch test reaction. The overall prevalence was similar in boys and girls, across age groups, and in patients with and without atopic dermatitis. Statistically significant increases in contact allergy to fragrances and isothiazoliones were seen, whereas a decrease in nickel allergy was found. Conclusion: Allergic contact dermatitis continues to be a common disease in children, and is even significantly increasing for some allergens.